Classification of Therapeutic and Experimental Drugs for Brown Adipose Tissue Activation: Potential Treatment Strategies for Diabetes and Obesity - Mukherjee, Jogeshwar; Baranwal, Aparna; N. Schade, Kimberly (Current Diabetes Reviews, 2016)
Objective: Increasing efforts are being made towards pharmacologic activation of brown adipose tissue (BAT) in animals and humans for potential use in the treatment of obesity and diabetes. We and others have reported a number of animal studies using either experimental or therapeutic drugs. There are now efforts to translate these findings to human studies. The goal of this review is to evaluate the various drugs currently being used that have the potential for BAT activation. Methods: Drugs were classified into 4 classes based on their mechanism of action. Class 1 drugs include the use of β3 adrenoceptor agonists for BAT activation. Class 2 drugs include drugs that affect norepinephrine levels and activate BAT with the potential of reducing obesity. Class 3 includes activators of peroxisome proliferator-activated receptor-γ in pursuit of lowering blood sugar, weight loss and diabetes and finally Class 4 includes natural products and other emerging drugs with limited information on BAT activation and their effects on diabetes and weight loss. Results: Class 1 drugs are high BAT activators followed by Class 2 and 3. Some of these drugs have now been extended to diabetes and obesity animal models and human BAT studies. Drugs in Class 3 are used clinically for Type 2 diabetes, but the extent of BAT involvement is unclear. Conclusion: Further studies on the efficacy of these drugs in diabetes and measuring their effects on BAT activation using noninvasive imaging will help in establishing a clinical role of BAT.
Keywords: BAT